Facile synthesis of water‐dispersible magnetite nanorings from surfactant‐free hematite nanorings. (1st December 2016) - Zhang, Yifan; Liu, Xiaoli; Peng, Erwin; Li, Galong; Xiao, Wen; Zhang, Huan; Yu, Baozhi; Wu, Jianpeng; Luo, Yane; Fan, Haiming
Abstract : Surfactant‐free α‐Fe2 O3 nanorings (NRs) were directly converted into water‐dispersible Fe3 O4 NRs through a simple and straightforward approach. In this process, uniform α‐Fe2 O3 NRs obtained through hydrothermal synthesis method are firstly thermally reduced to hydrophobic Fe3 O4 NRs in the presence of hydrophobic oleic acid surfactant and non‐polar trioctylamine solvent (under a flow of 5% H2 /95% Ar). Subsequently, oxidative cleavage of oleic acid capping agent using sodium periodate oxidising agent is imparted to yield water‐dispersible Fe3 O4 NRs. As compared with the traditional solid‐state reduction in tube furnace, the obtained Fe3 O4 NRs using solution‐based reduction process can retain its original uniform ring shape with good crystallinity and well‐defined magnetic vortex domain. Moreover, with the presence of azelaic acid on the surface of hydrophilic Fe3 O4 NRs, antibody or drugs can be easily conjugated, which further boost its potential theranostics application. This work provides a convenient approach to convert surfactant‐free nanoparticle (NP) powders into water‐dispersible NPs colloidal solutions for various biomedical applications.